Validation, Content Validity, and Reliability of the Spanish SE-OAM Questionnaire: Assessing Nursing Self-Efficacy in Oral Anticoagulant Therapy Management - Juan Ramón de-Moya-Romero; Raquel Valera-Lloris; Elena Chover-Sierra; Laura Fernández-Puerta; Alexis Caballero-Bonafé; Antonio Martínez-Sabater (Clinics and Practice)
Background/Objectives: Oral anticoagulant therapy (OAT) has been prescribed for over seventy years to prevent thromboembolic complications associated with various conditions. The emergence of direct-acting oral anticoagulants (DOACs) has reduced the use of vitamin K antagonists (VKAs), but specific clinical scenarios still necessitate VKAs. Nurses play a crucial role in managing OAT, and their self-efficacy is essential for optimal patient outcomes. This study aims to validate and adapt the Nursing Self-Efficacy for Oral Anticoagulant Therapy Management (SE-OAM) questionnaire to Spanish (SE-OAM-SV) to assess nurses’ self-efficacy in managing OAT. Methods: A methodological design was employed to develop the validity and reliability of the SE-OAM-SV. The process included translation and back-translation, expert review, and a pilot study. Content validity was analyzed using the content validity index (CVI), modified kappa coefficient, and Aiken’s V. A descriptive cross-sectional study was conducted with 100 nurses across Spain to test the SE-OAM-SV and identify comprehension issues. Internal consistency was assessed via Cronbach’s alpha. Results: The translation process highlighted some items requiring clarification, which were resolved through expert consultation. The SE-OAM-SV demonstrated adequate content validity with a global CVI of 0.86. The pilot study revealed an average participant age of 41.3 years and 17.3 years of professional experience. The SE-OAM-SV showed high internal consistency with a Cronbach’s alpha of 0.96. The average score of participants on the SE-OAM-SV was 56.8 points, indicating room for improvement in all aspects of the scale. Conclusion: The SE-OAM-SV is a reliable and valid tool for measuring nurses’ self-efficacy in managing OAT in Spanish-speaking communities. This tool can facilitate the development of educational programs and public policies to enhance nurses’ self-efficacy and improve patient outcomes. The availability of the SE-OAM-SV supports larger-scale studies and validation in other Spanish-speaking countries.